Aged care services for Indigenous people in the Australian Capital Territory and surrounds:analysing needs and implementing change - Phyll Dance; Roslyn Brown; Gabriele Bammer; Beverly Sibthorpe (Elsevier, 2004)
Abstract Objective: To ascertain and meet current and anticipated needs for residential care and other services by older Indigenous people in the Australian Capital Territory (ACT) and region. Methods: With advice from a reference group, qualitative and quantitative data were gathered from 98 older (45 years and over) Indigenous people in the ACT and region during 1999/2000. Indigenous and non‐Indigenous researchers worked closely throughout all phases of the research. We helped participants with immediate problems identified during the interviews and worked directly with the Government funding body to implement the findings. Results: No one expressed a current need for residential services. In terms of future needs, 50% of respondents favoured an arrangement where an existing mainstream provider of aged care accommodated a cluster of Indigenous people in the same facility as non‐Indigenous people. Thirty‐two per cent preferred an Indigenous‐run organisation. Our study also revealed a broad range of health problems and needs. Assessment using the Resident Classification Scale showed that 70% required a low level of care and 4% needed a high level of care. Conclusion: The research identified the needs and provided a health profile of older Indigenous people in the ACT and region. This then provided policymakers with evidence on which they acted to provide appropriate aged care services. Implications: Collaboration between Indigenous and non‐Indigenous researchers can access high‐quality information, and partnership between researchers and policymakers can improve Indigenous services.